Characters in Traditional Games; Analysis of Literature Related to Character Values Developed in Children Through Traditional Games - Nurhidayah, Nurhidayah; Lumbantobing, Panni Ance; Roziah, Roziah; Santi, Yulia; Ahmadi, Dedi (Universitas Trunojoyo Madura, 2024)
Traditional games are folk games that are inherited or developed from generation to generation in a particular area or culture. Traditional games are usually played in groups indoors or outdoors using simple equipment available in the surrounding environment with a fun nature. This study aims to identify and analyze children's characters developed through the application of traditional games. The type of qualitative research with descriptive analysis methods. Literature review of relevant journal articles from Google Scholar , articles are limited to publications in 2024 with the search keywords